2015
DOI: 10.1155/2015/193721
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of 3D Crack Growth in Transparent Rock-Like Material Containing Preexisting Flaws under Compression

Abstract: Mechanical behavior of 3D crack propagation and coalescence is investigated in rock-like material under uniaxial compression. A new transparent rock-like material is developed and a series of uniaxial compressive tests on low temperature transparent resin materials with preexisting 3D flaws are performed in laboratory, with changing values of bridge angleβ(inclination between the inner tips of the two preexisting flaws) of preexisting flaws in specimens. Furthermore, a theoretical peak strength prediction of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Some scholars have studied the crack propagation process from the wing crack reaching the limited length to the sample fracture and found that there was still a crack propagation process from the wing crack propagation to the sample failure. Tang et al (2015) found that after the wing crack propagation reached 1.5 times the prefabricated crack radius, many microcracks appeared in the crack‐free zone of the sample. These microcracks propagated and merged with the secondary cracks and finally penetrated the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have studied the crack propagation process from the wing crack reaching the limited length to the sample fracture and found that there was still a crack propagation process from the wing crack propagation to the sample failure. Tang et al (2015) found that after the wing crack propagation reached 1.5 times the prefabricated crack radius, many microcracks appeared in the crack‐free zone of the sample. These microcracks propagated and merged with the secondary cracks and finally penetrated the sample.…”
Section: Discussionmentioning
confidence: 99%
“…ere are several types of transparent similar materials commonly used by researchers to simulate rocks, including ice [18], PMMA [19][20][21][22], and resin materials [23][24][25][26], and among which PMMA and resin materials are the most widely used. However, resin materials compared with PMMA have become a hotspot in the development of transparent rock-like materials due to their strong plasticity.…”
Section: Selection Of Raw Materialsmentioning
confidence: 99%
“…Because of the low homogeneity of shale, researchers at home and abroad pay little attention to crack initiation and propagation, and most of them focus on other rocks or rock-like materials. Li et al , studied the progressive fracture behavior of brittle lithologic rocks, such as shale and granite. Lajtai divided the failure process of rock materials under uniaxial compression into six stages.…”
Section: Introductionmentioning
confidence: 99%